A profile approach to impulsivity in bipolar disorder: the key role of strong emotions. (18th April 2013) - Muhtadie, L.; Johnson, S. L.; Carver, C. S.; Gotlib, I. H.; Ketter, T. A.
<x xml:space="preserve">Abstract</x> Objective Bipolar disorder has been associated with elevated impulsivity – a complex construct subsuming multiple facets. We aimed to compare specific facets of impulsivity in bipolar disorder, including those related to key psychological correlates of the illness: reward sensitivity and strong emotion. Method Ninety‐one individuals diagnosed with bipolar I disorder (inter‐episode period) and 80 controls completed several well‐validated impulsivity measures, including those relevant to reward (Fun‐seeking subscale of the Behavioral Activation System scale) and emotion (Positive Urgency and Negative Urgency scales). Results Bipolar participants reported higher impulsivity scores than did controls on all of the impulsivity measures, except the Fun‐seeking subscale of the Behavioral Activation System scale. Positive Urgency – a measure assessing the tendency to act impulsively when experiencing strong positive emotion – yielded the largest group differences: F(1, 170) = 78.69, P < 0.001, partial η2 = 0.316. Positive Urgency was also associated with poorer psychosocial functioning in the bipolar group: ΔR2 = 0.24, b = −0.45, P < 0.001. Conclusion Individuals with bipolar I disorder appear to be at particular risk of behaving impulsively when experiencing strong positive emotions. Findings provide an important first step toward developing a more refined understanding of impulsivity in bipolar disorder with the potential to inform targeted interventions.